Association of timing of menarche with depressive symptoms and depression in adolescence: Mendelian randomisation study. (January 2017) - Sequeira, Maija-Eliina; Lewis, Sarah J.; Bonilla, Carolina; Smith, George Davey; Joinson, Carol
Abstract : Background: Observational studies report associations between early menarche and higher levels of depressive symptoms and depression. However, no studies have investigated whether this association is causal. Aims: To determine whether earlier menarche is a causal risk factor for depressive symptoms and depression in adolescence. Method: The associations between a genetic score for age at menarche and depressive symptoms at 14, 17 and 19 years, and depression at 18 years, were examined using Mendelian randomisation analysis techniques. Results: Using a genetic risk score to indicate earlier timing of menarche, we found that early menarche is associated with higher levels of depressive symptoms at 14 years (odds ratio per risk allele 1.02, 95% CI 1.005–1.04, n =2404). We did not find an association between the early menarche risk score and depressive symptoms or depression after age 14. Conclusions: Our results provide evidence for a causal effect of age at menarche on depressive symptoms at age 14.